A new species of large Hemiandrus ground wētā (Orthoptera: Anostostomatidae) from North Island, New Zealand - Trewick SA (Magnolia Press, 2021)
A new species of Hemiandrus ground wētā is described from North Island, New Zealand. Hemiandrus jacindasp. nov.is larger and more brightly coloured than other species in the region, but appears to be scarce and restricted to remnant native forest habitat.
Keywords: Orthoptera, Anostostomatidae, Hemiandrus, ground wētā, new species, North Island, New Zealand, Jacinda Ardern; Animals; Ecosystem; Forests; New Zealand; Orthoptera